Aloe Vera–Derived Gel-Blended PHBV Nanofibrous Scaffold for Bone Tissue Engineering. Issue 8 (August 2020) - Tahmasebi, Aylin; Shapouri Moghadam, Abbas; Enderami, Seyed Ehsan; Islami, Maryam; Kaabi, Mohamad; Saburi, Ehsan; Daei Farshchi, Amir; Soleimanifar, Fatemeh; Mansouri, Vahid
Abstract : Today, composite scaffolds fabricated by natural and synthetic polymers have attracted a lot of attention among researchers in the field of tissue engineering, and given their combined properties that can play a very useful role in repairing damaged tissues. In the current study, aloe vera–derived gel-blended poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanofibrous scaffold was fabricated by electrospinning, and then, PHBV and PHBV gel fabricated scaffolds characterized by scanning electron microscope, protein adsorption, cell attachment, tensile and cell's viability tests. After that, osteogenic supportive property of the scaffolds was studied by culturing of human-induced pluripotent stem cells on the scaffolds under osteogenic medium and evaluating of the common bone-related markers. The results showed that biocompatibility of the PHBV nanofibrous scaffold significantly improved when combined with the aloe vera gel. In addition, higher amounts of alkaline phosphatase activity, mineralization, and bone-related gene and protein expression were detected in stem cells when grown on PHBV-gel scaffold in comparison with those stem cells grown on the PHBV and culture plate. Taken together, it can be concluded that aloe vera gel–blended PHBV scaffold has a great promising osteoinductive potential that can be used as a suitable bioimplant for bone tissue engineering applications to accelerate bone regeneration and also degraded completely along with tissue regeneration.